Glycosylphosphatidylinositol-Anchored Proteins in Arabidopsis and One of Their Common Roles in Signaling Transduction - Zhou, Ke (Frontiers in Plant Science, 2019)
Diverse proteins are found modified with glycosylphosphatidylinositol (GPI) at their carboxyl-terminus (C-terminus) in eukaryotes, which allows them to associate with membrane lipid bilayers and anchored on the external surface of plasma membrane. GPI-anchored proteins (GPI-APs) play crucial roles in various processes, and more and more GPI-APs have been identified and studied. In this review, the previous genomic and proteomic predictions of GPI-APs in Arabidopsis have been updated, which reveals their high abundance and complexity. From studies of individual GPI-APs in Arabidopsis, certain GPI-APs have been found associated with partner receptor like kinases (RLKs), targeting RLKs to their subcellular localization, and helping to recognize extracellular signaling polypeptide ligands. Interestingly, the association might also be involved in ligand selection. The analyses suggest that GPI-APs are essential and widely involved in signal transduction through association with RLKs.